Data basics with databases - the wonders of data material - Karcher, Stefan (Interdisciplinary forum of digital textual sciences, 2018)
Vacation time is over and - which is a bit surprising for PhD students - I had much time to think about my dissertation and my academic future. I did some researches and picked up many new in…